A SCOPING REVIEW PROTOCOL TO MAP THE EVIDENCE ON SELF-REPORTED HEALTH AND NEUROTICISM IN OLDER ADULTS - Meire Cachioni; Vanessa Alonso; Gabriela Cabett Cipolli; Ruth Caldeira de Melo; Constança Paúl (Brazilian Society of Geriatrics and Gerontology, 2021)
OBJECTIVE: To identify the evidence on self-reported health and neuroticism in older adults. METHODS: Indexed literature published in English, Spanish and Portuguese will be systematically searched and retrieved from 10 databases; reference lists from included studies will be manually searched. Two authors will independently screen titles, abstracts, and full texts against the eligibility criteria. A customized data extraction form will be used to perform data extraction of the included studies, which will be: studies written in English, Portuguese, and Spanish; studies of older adults aged 55 years or over (mean age is 60 years at least); studies of community-dwelling older adults; studies that evaluated both self-reported health and personality; studies that evaluated self-reported health and personality with validated instruments; observational, review, and intervention studies. RESULTS: The results will be presented in a tabular format, accompanied by a narrative summary.